Evaluation of the biological activities of avocado seed and peel extracts (Persea americana) - Hồ, Nguyễn Thanh Trúc; Nguyễn, Thị Ngọc Phương; Nguyễn, Hồng Ngân; Lê, Huỳnh Hân; Đỗ, Tấn Khang; Trần, Ngọc Quý (Hue University Journal of Science: Natural Science, 2026)
Avocado peels and seeds are beverage processing residues that have a negative impact on the environment. However, they contain many valuable biological compounds. This study was conducted to investigate the presence of bioactive components, quantify the total phenolic (TPC) and flavonoid (TFC) contents and evaluate the antioxidant and antibacterial activities of ethanol extracts from avocado peels and seeds. Results from the qualitative assessment revealed that both extracts contained crucial biological compounds such as phenolic, flavonoid, saponin, steroid, and tannin. Specifically, the total flavonoid content of avocado seeds (436.13±14.84 mg QE/g extract) was greatly higher than that of peel (338.17±22.27 mg QE/g extract). Besides, evaluating the antioxidant capacity using DPPH, the avocado seed extract demonstrated markedly stronger antioxidant activity, 9.3-fold greater than the peel extract. Similarly, in the ABTS⁺ radical scavenging assay, the seed extract exhibited a lower IC₅₀ value (194.04 ± 8.02 µg/mL), about 1.8 times more potent than the peel extract (357.85 ± 12.32 µg/mL). At the concentration of 200 mg/mL, the avocado seed extract demonstrated inhibitory effects against both Gram-positive (Cutibacterium acnes, formerly Propionibacterium acnes) and Gram-negative (Escherichia coli) bacteria with inhibition zone diameters were 13.50±1.32 mm and 11.75±0.75 mm, respectively.